Readiness to the privatization of the health system in Saudi Arabia: Translation and factor analysis of Readiness to Organizational change (ROC) scale - Ahmed Ali Alasiri; Qi Zhang (PLoS ONE, 2025)
Background The Kingdom of Saudi Arabia (KSA) began a major transformation as a part of version 2030 for its health system. These reform initiatives aim to privatize health services and improve efficiency. Despite this meaningful change, there is a knowledge gap in how healthcare providers prepare for or perceive this shift. Specifically, there has been a lack of validation of Arabic instruments that gauge the individual readiness to this change. This study bridges the gap by localizing and validating the Readiness to Organizational Change scale (ROC) to provide empirical evidence and to understand adaptability for the KSA context. Method The study aimed to test and validate a tool that can be used to assess the ability of individuals to embrace the change initiatives among healthcare providers. A cross-sectional study was conducted in a public healthcare setting that included allied healthcare providers and physicians and excluded the administration staff. Ethical approval was obtained, and the questionnaire was distributed among participants electronically. Result There were 296 participants who completed the survey, with (78.0%) being male and they were between 25–35 years old, while the females represented (22%). The majority had less than 10 years’ experience and were married (88.2%). The face and content validity showed an excellent result for Arabic context S-CVI/AVE = 0.97. The inter-item correlation revealed a significant value (p < 0.001), which confirmed convergent validity, and Factor analysis assessed the adequacy of sampling (KMO = 0.77). The Exploratory Factor Analysis (EFA) extracted seven factors describing 74.6% of the total Variance, with an adequate value of commonalities for most items. Conclusion The Arabic version of ROC is a valid and reliable scale for assessing readiness among healthcare providers in the context of KSA. This translated version can provide insightful information and facilitate the transition of the health system in KSA and achieve the healthcare vision of 2030.